TEORI PERTUKARAN SOSIAL TENTANG FENOMENA DAKWAH DI EKS LOKALISASI DADAPAN - Ulum, Muhammad Syahrul; Warda, Alfa; Elina, Zuris Dwi; Ardiana, Ilmi Sephia (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2021)
This study aims to find out how the role of the preacher in bringing changes to the social conditions of the people who used to work in the Dadapan prostitution localization, Kediri City. Da'i plays an important role as a propagator of religion to protect the community. Thus, the relationship between the preacher and his community must be close regardless of the background or social conditions of the community. This research uses a qualitative approach with a case study method and is equipped with George Homans' social exchange theory, namely as an analytical tool to understand and seek clarity of cases so that researchers know more clearly about the phenomenon of da'wah in the ex-Dadapan localization community. The results of this study conclude that the da'wah process that occurs in Dadapan Village in social exchange theory explains that they are willing to interact when the interaction produces benefits for themselves. Therefore, in the dynamics of increasing religious understanding in the ex-Dadapan localization, it is necessary to have a reward given so that people want to interact in discussing religious studies.